The question of methodology in the science of Maqasid Al-Shari'ah (objectives of Islamic Law) - Soualhi, Younes (IIUM Institute of Islamic Banking and Finance, 2009)
This research addresses two methodological problems that seem to hinder the development of the concept of human welfare (public interest) in Islamic debate on whether maqasid is a philosophy or a method. The research tries to argue that masaqid moved from philosophy to method in order to revitalize the methods of inference in Islamic Jurisprudence. However, as the paper argues, the new position of maqasid as a method had little effect on Shatibi (d.14 century A.D) onwards. The latter's legal acumen is widely accredited with propounding a full-fledged theory on maqasid. In the second part of the research, we addressed the second problem which is the inadequancy featuring recent attempts by modern Muslim scholars and writers to formulate new concepts and present them as universal objectives of Islamic Jurisprudence. The research dealt critically with these new concepts, concluding that they have not been methodologically confirmed or proven as they are simply attributes of Islamic law but not necessarily the ultimate ends Shari'ah.